Hormonal Status of Aged Rats with Diet-Induced Obesity After Umbilical Cord Blood Administration - Bondarenko, Olena; Babiychuk, Vladyslav; Babiychuk, Lyudmyla (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):307